The Role of Teachers in Improving the Learning Process with the TGT (Team Games Tournament) Learning Model at SMP Methodist 9 Medan - Saragih, Oktavia Anjelina; Sianipar, Rosaria Anastasya; Sitanggang, Ade Tamaria (JUPE : Jurnal Pendidikan Mandala, 2023)
This research aims to find out how the learning process is in class using the TGT (Teams Games Tournament) learning model. TGT is a learning model that is carried out by learning and playing at the same time which actively involves students so that the learning process is effective and not boring. The method used in this research is a qualitative descriptive method. The researchers carried out data collection techniques by means of observation, interviews and documentation studies. Researchers observed the students' learning process using the TGT (Teams Games Tournament) learning model. Based on the results of the research at Medan Methodist Middle School 9, the learning process in class looked more enjoyable. TGT invites students to think critically and quickly, students are trained in speed and alertness in completing games in the TGT learning model because the teacher also gives a time limit for working on questions using the TGT learning model. Teachers and students are both active in implementing the TGT model in order to obtain maximum student learning outcomes.